Ecosystem services as a ballast to guide sustained economic growth by biodiversity conservation actions - Reale, Ricardo; Ribas, Luiz César [UNESP]; Lindenkamp, Teresa Cristina Magro (Elsevier, 2022)
Biodiversity loss reduces ecosystems productivity generating negative impacts on the global economy. Even though the economy is dependent on biodiversity or its ecological processes, few companies develop Biodiversity Conservation Actions (BCA) to benefit ecosystems, despite the growing number of sustainable companies worldwide. Here, we investigated the relationship between sustainability and biodiversity conservation of five sustainable corporations which controls more than 1,130,000 ha in five Brazilian biomes. We hypothesised that sustainable companies develop BCA to mitigate their negative environmental impacts and stimulate the refill of ecosystem services they had used. We analysed 5420 pages of annual sustainable reports between 2011 and 2018, qualifying and quantifying BCA indicated by each year companies' reports. We discovered that 90% of the units did not mitigate any negative environmental impacts. We found no BCA that included all productive units of each company, finding that most of the conservation actions were concentrated in few areas, most of them required by law. Companies are most concerned with how to economise costs of Environmental Management Systems than rebuild the ecosystems. We show a possibility to interrupt the “Jevons Paradox” by implementing BCA into the centre of the sustainability tripod's thinking. Finally, once BCA benefits the ecosystem services, they should be used as a ballast to validate sustained economic growth that respects the current and future generations.
Keywords: Biodiversity conservation; Ecosystem services; Environmental impacts; LIFE certification; Sustainability